2018
DOI: 10.1002/ccr3.1916
|View full text |Cite
|
Sign up to set email alerts
|

Eltrombopag in long‐term management of pediatric thrombocytopenia

Abstract: Key Clinical MessageEltrombopag is a thrombopoietin receptor agonist that may be effective in a broad range of thrombocytopenias of distinct etiology. We have observed rapid, robust, and sustained responses to eltrombopag in two young patients with refractory thrombocytopenia, one with primary immune thrombocytopenia and the other with Evans syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Two small prospective studies identified around 30% of patients who were able to completely discontinue eltrombopag for at least 12 weeks while maintaining hemostatic platelet counts [10,11]. These rates of therapy-free responses (TFRs) are in line with those reported in adult and pediatric patients treated with TPO-RA [12][13][14][15][16][17][18][19][20][21][22]. Although to date we still cannot identify on which patients this approach is likely to be most successful, a complete response to low doses of TPO-RA and a diagnosis of ITP < 1 year could lead to higher TFRs [15,23].…”
Section: Introductionmentioning
confidence: 58%
“…Two small prospective studies identified around 30% of patients who were able to completely discontinue eltrombopag for at least 12 weeks while maintaining hemostatic platelet counts [10,11]. These rates of therapy-free responses (TFRs) are in line with those reported in adult and pediatric patients treated with TPO-RA [12][13][14][15][16][17][18][19][20][21][22]. Although to date we still cannot identify on which patients this approach is likely to be most successful, a complete response to low doses of TPO-RA and a diagnosis of ITP < 1 year could lead to higher TFRs [15,23].…”
Section: Introductionmentioning
confidence: 58%
“…Although eltrombopag is currently approved as a second‐line approach to achieve a hemostatic platelet count, recent studies suggest that it has value as a prophylactic and primary treatment for different thrombocytopenias 14 . As suggested by Matthys et al, higher doses of eltrombopag may be required to treat thrombocytopenia secondary to myelosuppressive therapies and for other future indications 7 .…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 10 years after its initial approval for adult chronic ITP, eltrombopag was approved to treat pediatric patients with chronic ITP [ 2 , 3 ]. Long-term safety data on the use of eltrombopag in children are limited, and studies in adults have not revealed a clinically significant increase in the incidence of thrombosis [ 3 ].…”
Section: Introductionmentioning
confidence: 99%